Binge eating in obesity: Mainland Portugal and São miguel, Azores - Albergaria,Rita (2017)
This study aimed to investigate if binge eating-BE in individuals with obesity is influenced by their eating behaviour, social support satisfaction, healthcare, lifestyle and sociodemographical variables. It also aimed to compare BE and body mass index-BMI between individuals from mainland Portugal (n=117) and São Miguel, Azores (n=70) - cluster of islands with the largest national obesity incidence. Participants completed the Binge Eating Scale, the Dutch Eating Behaviour Questionnaire and the Social Support Satisfaction Scale. It was used as a modelling of structural equations to construct the structural model, having BE as dependent variable. Emotional eating (β=.26;p<.001), external eating (β=.2;p<.001) and satisfaction with support from friends (β=-.14;p=.004) predict the severity of BE. Also the level of educational level was associated to BE (β=-.11;p<.001). There was no association between BE and BMI (β=.003;p=.68) or between individuals from mainland Portugal and São Miguel (t(115,897)=-1.38;p=.17), contrary to the BMI (t(184,538)=3.57;p=.001). Interventions that promote adaptive strategies for management of emotional and external eating are suggested and also the development of friends network support in combination with health activities to attenuate the severity of BE. The absence of differences between the samples from mainland Portugal and the islands in relation to BE raises the hypothesis of other variables being able to explain the differences between the prevalence of obese individuals, other than the ones studied.